Loss of BRG1 (SMARCA4) Immunoexpression in a Pediatric Non-Central Nervous System Tumor Cohort. (April 2020) - Saunders, Jessica; Ingley, Katrina; Wang, Xiu Qing; Harvey, Melissa; Armstrong, Linlea; Ng, Tony; Dunham, Christopher; Bush, Jonathan
Malignant rhabdoid tumors and atypical teratoid/rhabdoid tumors of the central nervous system are primitive malignancies associated with a poor prognosis. These tumors have previously been characterized by inactivation of the switch/sucrose nonfermenting (SWI/SNF) chromatin remodeling complex protein integrase interactor 1 (INI1), encoded by the SMARCB1 gene. In the last decade, sporadic publications have shown that a different SWI/SNF protein, brahma-related gene 1 (BRG1), encoded by the SMARCA4 gene, is associated with a similar rhabdoid phenotype and possible germline mutation termed rhabdoid tumor predisposition syndrome type 2. We sought to determine the presence of BRG1 expression in pediatric embryonal tumors. Using a local tissue microarray consisting of 28 tumors diagnosed as having an undifferentiated, polyphenotypic, or rhabdoid morphology, expression of BRG1 by immunohistochemistry was performed. Four cases showed loss of INI1, while 3 of the remaining 24 cases demonstrated loss of BRG1. Two cases were diagnosed as soft tissue sarcomas, and 1 case was diagnosed as a small cell carcinoma of the ovary, hypercalcemic type. Survival ranged from less than 6 months after diagnosis to more than 5 years at the time of last follow-up. In conclusion, we demonstrate that BRG1 immunohistochemistry is a useful second-line immunostain for the workup of undifferentiated, polyphenotypic or rhabdoid pediatric tumors that demonstrate retained expression of INI1.